Isolating defensive corporate ESG effects: Evidence from purely domestic anti-COVID-19 measures - Goodell, J.W.; Corbet, S.; Hou, Y.; Hu, Y.; Oxley, Leslie (2024)
Few studies investigate whether ESG mitigates the harmful effects of changes in firms’ external environments. We evidence that ESG mitigated the impact of COVID-19 work-from-home and workplace prescriptions amongst several other pandemic-related government regulatory interventions, even when controlling for firm size. In a novel approach, we apply scrutiny of firms to restrict our cross-national sample to only firms with no cross-border trade, that is, explicitly domestically focused operational processes irrespective of the endpoint of corporate sales, enhancing methodological robustness. Consequently, we isolate an ESG effect. Results indicate the existence of a premium during the onset of each analysed national pandemic experience, particularly pronounced for those corporations that had achieved more substantiative ESG-based preparation and development before the onset of the COVID-19 pandemic.